2011
DOI: 10.1299/jbse.6.343
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Object Transfer: Effect of Observing Different Part of the Object on the Cooperative Task Smoothness

Abstract: Designing robots with human characteristics is a great challenge to researcher to fulfill the needs of robotic technology in human occupied environment. This research aims to enable a smooth and natural cooperative object transfer by a human hand and a robot manipulator mimicking the same task performed by two humans. Prior to the development of the human-robot system, investigation on characteristics which generate a smooth cooperative object transfer in a human-human system is crucial. Perceiving certain par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Results on the cooperation of human dyads suggest an object-centered formulation of the desired path, as they achieve better tracking performance in a cooperative task when they have common visual access to the central part of a manipulated object (Salleh et al, 2011). Thus, the desired motion of the manipulated object can be intuitively represented by an objectcentered trajectory as a result of a priori negotiation between the agents.…”
Section: System-theoretic Modeling Approachmentioning
confidence: 98%
“…Results on the cooperation of human dyads suggest an object-centered formulation of the desired path, as they achieve better tracking performance in a cooperative task when they have common visual access to the central part of a manipulated object (Salleh et al, 2011). Thus, the desired motion of the manipulated object can be intuitively represented by an objectcentered trajectory as a result of a priori negotiation between the agents.…”
Section: System-theoretic Modeling Approachmentioning
confidence: 98%
“…After removing duplicates ( n = 3,639 removed) and after title and abstract screening ( n = 5,435 removed), the full text of 18 studies were scanned and 10 studies were found to meet our eligibility criteria [ n = 8 removed: no active handover = 4 ( Salleh et al, 2011 ; Parastegari et al, 2018 ; Kato et al, 2019 ; Neranon, 2020 ), non-relevant outcome = 2 ( Korkiakangas et al, 2014 ; Carfì et al, 2019 ), no human kinematic or force data = 2 ( Xie and Zhao, 2015 ; Chan et al, 2020 )]. Thus, we included 10 studies in our systematic review that investigated the characteristics of human-human handover actions and their influencing factors, such as the handover object weight and availability of sensory information ( Mason and Mackenzie, 2005 ; Becchio et al, 2008 ; Gonzalez et al, 2011 ; Meyer et al, 2013 ; Hansen et al, 2017 ; Controzzi et al, 2018 ; Bekemeier et al, 2019 ; Cini et al, 2019 ; Döhring et al, 2020 ; Sutiphotinun et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%